EP.TU.991Developing as Future Leaders: A Systematic Review of Quality Improvement Training in Junior Doctors. (28th October 2021) - Aseem, Rabiya; Simillis, Costas; Smith, Jason; Arora, Sonal; Pawa, Nikhil
Abstract: Aims: Quality improvement (QI) training in Junior Doctors (JDs) is essential for providing High Quality Care for patients and facilitating organisational success. The aim of this study was to systematically review the evidence on QI training in JDs and determine the impact and effectiveness of training methods. Methods: A systematic review was conducted as per PRISMA guidelines. Searches were carried out using MEDLINE, EMBASE and HMIC for English-Language articles between January 2005 to December 2019. Selected articles underwent critical appraisal using the CASP criteria by two independent reviewers. A qualitative and thematic analysis was conducted. Results: 43 studies were identified in a range of medical and surgical specialities. Common QI methodology included theoretical and project-based curricula with content focussing on PDSA cycles, root causes analyses and project development. Majority of studies reported improved knowledge, leadership skills and satisfaction. Mentorship and coaching were highly valued, but few studies adhered to this practice. Few studies demonstrated increased QI engagement. Key themes identified (i) Effectiveness of QI training (ii) Barriers to engagement (iii) Organizational culture of fostering QI. Conclusion: There is growing mandate for training JDs in QI practices to enhance patient care. QI curricula targeting JDs have demonstrated improved knowledge and leadership skills. Nonetheless, significant barriers in QI engagement endure. Additional research is required to combat disengagement and assess sustainability of QI interventions in JDs. We further aim to introduce a pilot QI training programme for surgical JDs to enhance leadership skills.